Development of a digital-based sit and reach box for measuring body flexibility - Wicaksono Ari Wibowo; Wahyu Indra Bayu; Iyakrus Iyakrus; Fauziah Nuraini Kurdi; Hartati Hartati; Syafaruddin Syafaruddin (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2023)
Technology and education development are expected to make teachers easier to create and produce learning media used practically and efficiently. This study used the research development (R&D) method proposed by Borg and Gall, consisting of ten research steps. It aimed to develop a preliminary product design for a digital-based flexibility test measuring instrument. This research produces a body flexibility measurement tool for physical education subjects, particularly physical fitness. The participants of this study were Tanjung Lago 1 Public Middle School students validated, revised, and tested on small and large scales. Three experts validated this research through a questionnaire of various kinds of questions, i.e.1) an expert in sports tests and measurements, namely a lecturer at PGRI Palembang University (94% in the very compatible category), 2) an expert in electrical media from C.V. Cometronica Palembang (82% very appropriate category), and 3) the teacher of Physical education from SMPN 1 Tanjung Lago (97% very proper category). The three experts reveal that an average of 91% of the digital-based sit and reach box applied to measure flexibility tests is worthy. It is supported by the statistical results of small-scale trials with normality tests of 0.200, homogeneity tests of 0.785, and paired sample t-tests of 0.785, statistical results of large-scale trials with normality tests of 0.200, homogeneity tests of 0.64, and paired sample t-test of 0.299. This study indicates that the digital-based sit and reach box tool developed and tested for meeting validity and effectiveness can be implemented in teaching and learning activities. Key words: development, flexibility, digital.